Political will in preserving natural resources in Kenya: policies on environmental protection - Shuriye, Abdi Omar (Islamic Centre for Research and Development, Australia, 2010)
There are adequate laws and policies on environmental protection in Kenya. The National Environment Management Authority (NEMA) of Kenya was established under the Environmental Management and Coordination Act (EMCA) No. 8 of 1999, as the principal instrument of government in the implementation of all policies relating to the environment in Kenya. Obviously the act is new but the news about environmental protection is quickly developing roots in the minds of many Kenyans. In fact, governmental and non-governmental environmental activities have being in place for decades. But the formation of Green Belt Movement and the Nobel Peace Prize won by its founder Wangari Maathai in 2004 was a landmark for non-governmental environmental activities in Kenya. NEMA, a government body on environment became operational on 1st July 2002 following the merger of three government departments, namely: the National Environment Secretariat (NES), the Permanent Presidential Commission on Soil Conservation and Afforestation (PPCSCA), and the Department of Resource Surveys and Remote Sensing (DRSRS). However, following government restructuring in March 2003, DRSRS reverted to its departmental status under the then Ministry of Environment and Natural Resources (MENR). The enactment of Environmental Management and Coordination Act (EMCA), 1999 was also a milestone in promoting sustainable environmental management in Kenya. The Act provides for the harmonization of about 77 sectoral statutes, which address aspects of the environment. Environmental problems in Kenya include deforestation and soil erosion caused by growing population and increased demands for food production. The aim of this paper is to assess the political will of Kenyan government in protecting ecological and environmental related recourses.